Menjadi Indonesia : 13 abad eksistensi Islam di bumi Nusantara - Hidayat, Komaruddin, 1953-; Ahmad Gaus AF, 1968-; Yayasan Festival Istiqlal (Jakarta, Indonesia) (Jakarta : Mizan bekerjasama dengan Yayasan Festival Istiqlal, 2006)
History of Islam in Indonesia; collection of articles
Keywords: Islam -- Indonesia -- History; Islam and state -- Indonesia; Islam and politics -- Indonesia -- History; Indonesia -- Politics and government